Gadolinium-Coated Mesoporous Silica Nanoparticle for Magnetic Resonance Imaging - Li, Zhongtao; Guo, Jing; Zhang, Mengmeng; Li, Guohua; Hao, Liguo (Frontiers in Chemistry, 2022)
Abstract:Magnetic resonance molecular imaging can provide anatomic, functional and molecular information. However, due to the intrinsically low sensitivity of magnetic resonance imaging(MRI), powerful image information for image diagnosis are required to generate high-performance MRI contrast agents. Herein, we describe a novel T1 contrast agent with magnetic-imaging properties facilitated by the gadolinium oxide (Gd2O3) doping of mesoporous silica nanoparticles (MSN). The size,morphology, composition,MRI relaxivity (r1), surface area and pore size of these nanoparticles(NPs) were evaluated following their conjugation to Gd2O3 to produce Gd2O3@MSN. This unique structure led to a significant enhancement in T1 contrast with longitudinal relaxivity (r1) as high as 59.68 mM−1s−1. Gd2O3@MSN has a larger T1 relaxivity than commercial gadolinium diethylene triamine pentaacetate(Gd-DTPA), likely due to the geometrical confinement effect of the silica naniparticles. These results suggest that we have successfully prepared a novel high-performance T1 contrast agent,which may be a potential candidate for in vivo MRI.